Unhappy doctors? A longitudinal study of life and job satisfaction among Norwegian doctors 1994 - 2002 - Førde Reidun; Gulbrandsen Pål; Nylenna Magne; Aasland Olaf G (BMC, 2005)
Abstract Background General opinion is that doctors are increasingly dissatisfied with their job, but few longitudinal studies exist. This study has been conducted to investigate a possible decline in professional and personal satisfaction among doctors by the turn of the century. Methods We have done a survey among a representative sample of 1 174 Norwegian doctors in 2002 (response rate 73 %) and compared the findings with answers to the same questions by (most of) the same doctors in 1994 and 2000. The main outcome measures were self reported levels of life satisfaction and job satisfaction according to the Job Satisfaction Scale (JSS). Results Most Norwegian doctors are happy. They reported an average life satisfaction of 5.21 in 1994 and 5.32 in 2002 on a scale from 1 (extremely dissatisfied) to 7 (extremely satisfied). Half of the respondents reported a very high level of general life satisfaction (a score of 6 or 7) while only one third said they would have reported this high level of satisfaction five years ago. The doctors thought that they had a higher level of job satisfaction than other comparable professional groups. The job satisfaction scale among the same doctors showed a significant increase from 1994 to 2002. Anaesthesiologists and internists reported a lower and psychiatrists and primary care doctors reported a higher level of job satisfaction than the average. Conclusion Norwegian doctors seem to have enjoyed an increasing level of life and job satisfaction rather than a decline over the last decade. This challenges the general impression of unhappy doctors as a general and worldwide phenomenon.